Comparative Assessment of Modulation Strategies in Modular Multilevel Converters: An Attempt for a Better Compromise Between the Efficiency and Capacitor Voltages' Dispersion - Anthony Abdayem; Jean Sawma; Adrian Beneit; Ramon Blasco-Gimenez; Flavia Khatounian; Eric Monmasson (IEEE Open Journal of the Industrial Electronics Society)
Modulation techniques for Modular Multilevel Converters (MMCs) encounter a limit in the tradeoff between reducing the total harmonic distortion (THD) of the load current and minimizing the number of commutations, primarily due to traditional sorting algorithms. This article presents a novel sorting algorithm to address this challenge. This study compares six modulation methods for MMCs: Nearest Level Control (NLC), Integral Modulation (IM), and PWM using a traditional sorting algorithm, alongside their modified versions featuring the novel sorting algorithm. The effectivenss of each modulation technique discussed in this article is verified through experimental tests. The results show that the proposed modulation techniques utilizing the suggested sorting algorithm, effectively decrease the switching number while maintaining the THD of the load currents. However, there is a slight increase in the disparity of the capacitor voltages, which remains controllable. In addition, the study fills a gap in the literature by providing experimental evidence and a theoretical framework demonstrating the superior efficiency of IM over NLC through frequency analysis and experimental results. These findings highlight the potential of the proposed techniques to optimize the MMC performance.